1985
DOI: 10.1111/j.2042-3306.1985.tb02552.x
|View full text |Cite
|
Sign up to set email alerts
|

BCG treatment of periocular sarcoid

Abstract: Summary Twenty‐six horses and five mules with periocular sarcoids were treated with intralesional injections of a purified bacillus of Calmette and Guerin (BCG) cell walls in oil suspension. All sarcoids were cured and the horses and mules remained free from recurrence of sarcoid during the two‐year follow‐up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 12 publications
1
41
1
Order By: Relevance
“…Sarcoids are the most common skin tumors in horses [1–3], with prevalence rates ranging from 12.9 to 67% of all equine tumors [4, 5]. They appear as benign fibroblastic skin tumors, and are characterized by rare regression, invasiveness and high recurrence following surgery [6–8].…”
Section: Introductionmentioning
confidence: 99%
“…Sarcoids are the most common skin tumors in horses [1–3], with prevalence rates ranging from 12.9 to 67% of all equine tumors [4, 5]. They appear as benign fibroblastic skin tumors, and are characterized by rare regression, invasiveness and high recurrence following surgery [6–8].…”
Section: Introductionmentioning
confidence: 99%
“…Equine sarcoids are the most common skin tumours in equids worldwide (Jackson, 1936;Pascoe & Summers, 1981;Ragland et al, 1970) with reported prevalence rates ranging from 12.9 to 67 % of all equine tumours (Lavach et al, 1985). Six clinical types of sarcoid are recognized including occult, verrucouse, nodular, fibroblastic, mixed and malignant types (Knottenbelt, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained with repeated local administration of BCG in superficial bladder cancer in humans [2, 3, 5, 13, 20-22, 26, 27] and in sarcoids in horses [16,23,28,29,33] stimulated the present study of the effect of repeated treatment of BOSCC with BCG. Moreover, in a previous study of Klein et al [17] it was suggested that the success of the therapy might be correlated with the ability of the immune system to generate long-lasting BCG-specific memory.…”
Section: Introductionmentioning
confidence: 54%
“…Repeated intralesional injections of BCG in horses with fibro-epithelial tumours (equine sarcoids) resulted in complete cure in 50%-90% of the animals [16,23,28,29,33]. There was no recurrence after repeated treatment [16].…”
Section: Introductionmentioning
confidence: 96%